The emergence of NDM-1, IMP-7, IMP-26, IMP-62, IMP-76, VIM-4 and VIM-5 producing Pseudomonas aeruginosa strains, identification of a novel sequence type (ST3891) and analysis of virulence genes from a Malaysian tertiary hospital - Kalaivani Kalai Chelvam; Yue Min Lim; Cindy Shuan Ju Teh; Sasheela Ponnampalavanar; Jamuna Vadivelu; Vanitha Mariappan; Kumutha Malar Vellasamy (PLoS ONE, 2026)
Multidrug-resistant (MDR) Pseudomonas aeruginosa is a medically crucial nosocomial pathogen causing significant mortality in patients with weakened immune systems. It is sensitive to carbapenems such as meropenem and imipenem. However, recent research indicates the rise and rapid transmission of carbapenem-resistant P. aeruginosa (CRPA). This study analysed the phenotypic and genotypic traits linked with CRPA strains obtained from the University Malaya Medical Centre (UMMC), a Malaysian tertiary teaching hospital. MDR P. aeruginosa (n = 215) were isolated from the Medical Microbiology Diagnostic Laboratory (MMDL). The VITEK-2 automated system was used for antimicrobial susceptibility and data for susceptibility to various antimicrobial agents were retrieved from the MMDL database at the UMMC. The minimum inhibitory concentration (MIC) of the carbapenems (meropenem and imipenem) was analysed using the broth microdilution method. Pyocyanin, protease and biofilm assays were conducted to assess the phenotypic traits. Furthermore, polymerase chain reaction (PCR) was used to detect six virulence genes and three carbapenemase genes. P. aeruginosa strains that displayed high-level resistance to meropenem and imipenem showed an association with 140 strains (65.1%) that were strong biofilm producers (OD 570nm ≥ 3.0). The majority of the strains (73.5%) exhibited high to moderate pyocyanin production, while 95.3% were capable of secreting protease. Among the six virulence genes tested, most of the strains harboured the toxR (109/215, 50.7%) and algD (108/215, 50.2%) genes. The identification of carbapenem genes showed bla IMP (n = 24, 11.2%) followed by bla NDM (n = 16, 7.4%) and bla VIM (n = 4, 1.86%). A novel sequence type, ST3891 was discovered using multilocus sequence typing (MLST). The rising incidence of carbapenem-resistant strains is concerning, as carbapenems with antipseudomonal activity play a vital role in treating P. aeruginosa infections. Additionally, this study found a positive correlation between increased biofilm production and resistance to carbapenem in P. aeruginosa. This emphasises the importance of stringent infection control strategies, particularly considering the clonal dissemination of the high-risk ST235 clone and the identification of the novel ST3891 strain in Malaysia.